Pengaruh Pendidikan, Tenaga Kerja dan Kesehatan terhadap Kemiskinan (Studi Kasus pada Provinsi Bali) - Rahma Aprilia; Rr Retno Sugiharti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
The purpose of this study is to identify how education, labor, and health  affect poverty in Bali. The information used includes information on the school participation rate (SPR) of the population aged 16 to 18 years, the number of workers, and the number of public health facilities. The data is annual, for the period 2000 – 2021 taken from the website of the Bali Central Statistics Agency (BPS). The data was processed using the Eviews-10 application with the ECM-EG analysis method. The final results show (1) In the long run, only the Labor variable has a significant negative effect. Education and Health variables have a negative but not significant effect on poverty (2) In the short term, the variables of Education, Employment, and Health have a negative but not significant relationship in influencing poverty during the study period.